Association of apolipoprotein levels with peripheral arterial disease: a meta-analysis of literature studies. (18th September 2020) - Forte, Francesco; Calcaterra, Ilenia; Lupoli, Roberta; Orsini, Roberta Clara; Chiurazzi, Martina; Tripaldella, Maria; Iannuzzo, Gabriella; Di Minno, Matteo Nicola Dario
Abstract: Aims: Lower limb peripheral artery disease (PAD) is a leading cause of atherosclerotic cardiovascular disease (ASCVD). Discordant data are available on the association between apolipoprotein and PAD. We performed a meta-analyses on the association between apolipoprotein (apo)B, apoA-I, and apoB/apoA-I ratio with PAD. Methods and results: PubMed, Web of Science, Scopus databases were systematically searched. Studies providing data about apoB, apoA-I, apoB/apoA-I ratio in PAD subjects and non-PAD controls were included. Differences between PAD and non-PAD subjects were expressed as mean difference (MD) with pertinent 95% confidence intervals (95%CI). Twenty-two studies were included. Peripheral artery disease subjects showed higher apoB (MD: 12.5 mg/dL, 95%CI: 2.14, 22.87) and lower apoA-I levels (MD: −7.11 mg/dL, 95%CI: −11.94, −2.28) than non-PAD controls. Accordingly, ApoB/ApoA-I ratio resulted higher in PAD subjects than non-PAD controls (MD: 0.11, 95% CI: 0.00, 0.21). Non-HDL-C showed a direct association with the difference in apoB (z-value: 4.72, P  < 0.001) and an inverse association with the difference of apoA-I (z-value: −2.43, P  = 0.015) between PAD subjects and non-PAD controls. An increasing BMI was associated with an increasing difference in apoA-I values between PAD subjects and non-PAD controls (z-value: 1.98, P  = 0.047). Conclusions: Our meta-analysis suggests that PAD subjects exhibit increased apoB and reduced apoA-I levels, accompanied by an increased apoB/apoA-I ratio as compared with non-PAD controls.